Use of Technology in Monitoring the Performance of Ship Crews at Shipping Companies Using the Balanced Scorecard Theory and Expectancy Theory - Yusuf, Muhammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This research shows that the use of technology in monitoring the performance of ship crews can provide great benefits for shipping companies. Technology can help collect accurate and reliable data, simplify performance measurement, and speed up decision making. In addition, the theory of the Balanced Scorecard and Expectancy Theory can assist in strengthening the performance measurement system, fostering motivation in the crew, and encouraging companies to achieve better business goals. However, other factors such as leadership, organizational culture, and work environment also play an important role in influencing the performance of the crew. Good leadership and positive organizational culture can motivate the crew to achieve better performance. A safe and comfortable work environment can also improve the performance of the ship’s crew. In using technology, companies must also consider technological capabilities and organizational readiness to adopt them. In this case, the company needs to ensure that the technology used is in accordance with business needs and can be accessed and used easily by the crew. Overall, this journal is the importance of using technology and theory of the Balanced Scorecard and Expectancy Theory in monitoring the performance of crew members. However, other factors such as leadership, organizational culture, and work environment also affect the performance of the crew and need to be considered by shipping companies.